[PP.16.32] COMORBIDITIES OF HYPERTENSIVE PATIENTS HOSPITALIZED IN THE INTENSIVE CARE UNIT OF THE CLINICAL EMERGENCY HOSPITAL SF. IOAN (BUCHAREST). (September 2016) - Dediu, G.; Balaceanu, A.; Fronea, M.; Diaconu, C.; Aron, G.; Dina, I.
Abstract : Objective: To evaluate the frequency of arterial hypertension and associated comorbidities in patients hospitalized in the Intensive Care Unit of a University Clinical Emergency Hospital. Design and method: The descriptive study included 42 patients consecutively admitted between January 1st – March 1st, 2015. In every patient personal medical history, clinical exam, laboratory tests (blood sugar, lipids, creatinine, BUN), and ECG were performed. The statistical analysis was made using the SAS system. Figure. No caption available. Results: The distribution by sex in the group of study: 24 men (57.14%), 18 women (42.85%). The distribution of comorbidities: 32 pts with ischemic heart disease, 26 pts with arterial hypertension, 25 pts with chronic kidney disease, 15 pts with dyslipidemia, 14 pts with obesity, 14 pts with atrial fibrillation, 11 pts with type 2 diabetes. The other characteristics of patients are described in Table 1. Half of the study group had over 79.5 years old. We analyzed by Fisher's exact test whether the probability of hypertension in older patients (age >65 years) exceeds the probability of hypertension in patients younger than 65 years; the p-value of 0.64 did not support this hypothesis. 34% of patients had type 2 diabetes mellitus and from the diabetic patients 71% were hypertensive. 96.15% from hypertensive patients had ischemic heart disease. 62% of hypertensive patients had chronic kidney disease. 28.57% had stage 2 chronic kidney disease, 21.43% stage 3 and 9.52% stage 4. Only 12% of patients had dyslipidemia; all dyslipidemic patients were hypertensive. 21 % of patients with hypertension had atrial fibrillation and 40 % had nonalcoholic fatty liver disease (p-value <0.001). Conclusions: The frequency of arterial hypertension in our study was similar in patients > 65 years old and those < 65 years old. Diabetes was strongly associated with hypertension. Almost all hypertensive patients had ischemic heart disease. We have found a correlation between dyslipidemia and hypertension, but not between obesity and hypertension. Chronic kidney disease (stage 2 and 3) is a frequent comorbidity in hypertensive patients admitted in Intensive Care Unit.